Pembaharuan Dan Pembangunan Hukum Transportasi Di Era Disrupsi Melalui E-Governance - R.Desril (UIR Law Review, 2022)
This study aims to analyze Describing the Renewal and Development of Transportation Law in the Disruption Era and Discovering the Concept of Transportation E-Governance in the Disruption Era. This research is based on normative juridical research methods, which include research on positive law inventory, research on legal principles and research on law in concreto. Secondary data in this normative legal research are in the form of primary legal materials, secondary legal materials and tertiary legal materials. The results of this study are that transportation policies and regulations in the era of disruption require integrated and comprehensive regulations, it is necessary to realize E-governance of transportation law in the era of disruption. The Ministry of Transportation's policy to provide comprehensive transportation can be seen in the 2020-2024 National Transportation Master Plan. However, in the Master Plan there are no policies that lead to E-Governance as a response to the development of transportation in the era of disruption. So to perfect this Policy, Renewal and Development of Transportation Law in the Era of Disruption through E-Governance is needed. This is where the urgency of research with the title Transportation E-Governance: Design of Transportation Law Regulatory Models in the Disruption Era to find the Renewal and Development of Transportation Law in the Disruption Era and Formulate the Concept of Transportation E-Governance. Keywords: E-Governance, Transportation, Model, Regulation, Disruption.